Stabilization of bacterially expressed erythropoietin by single site-specific introduction of short branched PEG chains at naturally occurring glycosylation sites. Issue 6 (18th January 2016) - Hoffmann, E.; Streichert, K.; Nischan, N.; Seitz, C.; Brunner, T.; Schwagerus, S.; Hackenberger, C. P. R.; Rubini, M.
Abstract : Erythropoietin (EPO) with single small branched PEG chains installed by the Staudinger-phosphite reaction leads to enhanced solubility, stability and intact in vitro bioactivity. Abstract : The covalent attachment of polyethylene glycol (PEG) to therapeutic proteins can improve their physicochemical properties. In this work we utilized the non-natural amino acid p -azidophenylalanine (pAzF) in combination with the chemoselective Staudinger-phosphite reaction to install branched PEG chains to recombinant unglycosylated erythropoietin (EPO) at each single naturally occurring glycosylation site. PEGylation with two short 750 or 2000 Da PEG units at positions 24, 38, or 83 significantly decreased unspecific aggregation and proteolytic degradation while biological activity in vitro was preserved or even increased in comparison to full-glycosylated EPO. This site-specific bioconjugation approach permits to analyse the impact of PEGylation at single positions. These results represent an important step towards the engineering of site-specifically modified EPO variants from bacterial expression with increased therapeutic efficacy.